Retrieval of Analogs from Long-Term Memory: Explaining the Divergence Between Experimental and Naturalistic Studies - Trench, Juan Maximo (2014)
In contrast to the experimental tradition in the study of analogical retrieval, naturalistic studies in which participants have to retrieve their own source analogs suggest that retrieval does not require superficial similarities. However, two important limitations of naturalistic studies concern the unknown availabilities of close vs. distant matches in long-term memory and the use of retrieval measures vulnerable to report bias. In the present study we complemented the procedure followed in naturalistic studies with two additional controls: (1) a survey of naturally encoded sources available in Long-Term Memory prior to the experimental session, and (2) a measure of analogical retrieval less vulnerable to report bias. A comparison between the number of natural analogs that were available in memory and those that were retrieved during an analogy generation task demonstrated that retrieval of naturally encoded source analogs-just as retrieval of experimentally learned situations-is strongly constrained by superficial similarity.